Aplikasi Pestisida Nabati dan Trichokompos terhadap Penyakit Bercak Daun (Cercospora oryzae) pada Padi Beras Merah di Lahan Basah - Sahrul Gunawan; Ismed Setya Budi; Mariana Mariana (JURNAL PROTEKSI TANAMAN TROPIKA, 2023)
Cultivation of brown rice (Oryza nivara L.) in wetlands continues to expand because its consumers continue to increase. This study aims to determine the ability of Trichocompost and a solution of botanical pesticides from kalakai, babadotan and purun tikus in controlling brown spot disease caused by the fungus Cercospora oryzae on brown rice plants in wetlands. Based on the results of observations, the application of trichocompost and purunrat solution was able to reduce the incidence of leaf spot disease from 95.1% in controls to 76.5%. The results of disease intensity showed that the application of trichocompost and kalakai solution was able to reduce disease intensity from 19.55% in controls to 14.10%. The application of trichocompost and babadotan solution increased the number of grains of rice from 216.60 grains in the control to 243.20 grains. The application of Trichocompost and kalakai solution increased the weight of 100 grains from 1.79 g to 2.10 g. The application of only trichocompost, Trichocompost and kalakai solution, trichocompost and babadotan solution, and trichocompost and purunrat solution have the same ability to reduce the incidence and intensity of Cercospora disease. All treatments tested were unable to increase plant height growth.